Interprofessional Education in Critical Care: A Consensus Statement - Jane Harnischfeger; Cameron Knott; Paul Ross; Jenna Lang; Mya Cubitt; Matt Mason; Kate McCleary; Deb Massey (Bond University, 2021)
Interprofessional Education (IPE) is increasingly acknowledged as crucial for promoting and improving quality and safety in healthcare, building a collaborative, practice- ready workforce, and improving health outcomes. In the critical care environment, a Consensus Statement outlining best practice for IPE has been lacking. This absence of a best practice standard has hampered development, implementation, and evaluation of IPE activities in critical care. The Australia New Zealand Clinician Educator Network developed a Consensus Statement through a collaborative, multidisciplinary working group who met in person and online for the purposes of outlining the best practices underpinning IPE in critical care. These recommendations were developed for consideration by clinician educators in the critical care setting when planning, implementing, and evaluating IPE activities. This consensus statement recommends specific structural and processual requirements and evaluates outcomes using the domains of culture, education, quality and safety, based on current literature. The ultimate consequence of IPE in critical care is to improve patient outcomes and inform clinical education research, policies and procedures within a continuous improvement cycle.